Kebijakan Pembangunan Tol Laut dan Potensi Dampaknya pada Tinggalan Kapal Asing Bersejarah yang Karam di Wilayah Perairan Indonesia - Putra, Hutomo (UI Scholars Hub, 2019)
The construction of sea toll roads is one of the manifestations of President Jokowi’s superior program for strengthening Indonesia’s identity as a maritime country and to develop Indonesia as a whole from west to east. The necessity for sea toll road construction aims to improve the distribution of goods and trade commodities, particularly for the purpose of balancing the economic gap between the western and eastern regions of Indonesia. On the other hand, the construction of sea toll roads could possibly have an impact on archaeological objects, especially the remains of historic shipwrecks that have sunk and spread in several Indonesian territorial waters. Moreover, some of these remains are located on or adjacent to sea lane paths which will indirectly be affected by the deepening of the program in the context of the sea toll road construction. This paper aims to disseminate information about the tangible proofs of Indonesian cultural richness and long maritime history that have not been fully revealed and are threatened by potential damage and destruction if no necessary action is taken. Most importantly, this paper attempts to propose a strategy for constructing sea toll roads by taking into account the use and preservation of potential historical shipwreck remains which are still scattered in several territorial waters of Indonesia.